Best Answer

6x2-4x2+3 = 0 2x2 + 3 = 0 2x2 = -3 x2 = -3 / 2 this equation has imaginary roots x = +sqaureroot (3/2)i , -sqaureroot (3/2)i

where i = complex variable

Q: 6x to the power of 2 -4x to the power of 2 plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2

- 4X - 6X + 2 = 2(- 2X - 3X + 1) -------------------------that is all the factoring I can see to do here

2 - 4x - 2x + 4 = 6 - 6x

4x(4x^2 - 6x + 7)

Related questions

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2

- 4X - 6X + 2 = 2(- 2X - 3X + 1) -------------------------that is all the factoring I can see to do here

2 - 4x - 2x + 4 = 6 - 6x

4x(4x^2 - 6x + 7)

4x-6x = -2

Dividend: 6x^3+29x^2-40x-42 Divisor: 6x+5 Quotient: x^2+4x-10 Remainder: 8

-6x, -4x =

6x + 3 = 2x + 5 4x = 2 x=1/2

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

-6x + 5 = -4x + 19add 6x to both sides5 = 2x + 19subtract 19 from both sides-14 = 2xdivide both sides by 2-7 = x

6x + 8 = 6 6x = -2 x = -2/6 x = -1/3